Employee Performance at PT. Sinar Mas Sungai Bungur Estate Lahat as a Result of Career Development, Work Environment, and Compensation - Nisma Aprini (Departement of Socio-Economic Agricuture, Faculty of Agriculture, 2021)
Internally and externally, PT Sinar Mas Sungai Bungur Estate (SM SBE) faces a number of issues. Employee performance is impacted by this issue. The purpose of this study is to investigate the impact of career development, work environment, and compensation on the performance of PT Sinar Mas Sungai Bungur Estate Lahat personnel. This study uses the quantitative methodology and statistical analysis. Questionnaires, discussion focus groups, interviews, and secondary data were used to collect data. Multiple regression analysis, coefficient of determination, and hypothesis testing were applied in the data analysis. Career development variables (X1), work environment variables (X2), and compensation variables (X3) had no significant effect on performance, according to the findings (Y). As a result, the study's hypothesis that there is a significant impact on performance metrics has not been verified (Y).